1998
DOI: 10.1038/sj.onc.1202074
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic analysis of Vav reveals that an intact SH3 domain is required for transformation

Abstract: The vav proto-oncogene encodes a protein with multiple modulae domains that enable it to function as a mediator, linking tyrosine signaling to downstream events in hematopoietic cells. Circumstantial evidence suggests that protein-protein interactions exerted by two of these domains, the Src homology 2 (SH2) and the Src homology 3 (SH3), play an important role in the regulation of Vav activity. To study the relevance of the SH3 domain for the function of vav as a transforming gene, we have created several muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
(83 reference statements)
0
29
1
Order By: Relevance
“…We found that the transforming activities of the ⌬N-186 Vav SH3(W636K) and ⌬N-186 Vav SH3(W636K/W820K) mutants were decreased 3-6-fold, respectively. In contrast to the decreased activity described in a previous study (28), we found that the ⌬N-186 Vav SH3(820K) mutant showed an enhanced focus-forming ability. However, when we deleted the entire SH3/SH2/SH3 domain (⌬N-186 Vav⌬C), we were surprised to see that it was enhanced significantly in transforming activity.…”
Section: The Dh/ph/crd Is the Minimal Functional Transformingcontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that the transforming activities of the ⌬N-186 Vav SH3(W636K) and ⌬N-186 Vav SH3(W636K/W820K) mutants were decreased 3-6-fold, respectively. In contrast to the decreased activity described in a previous study (28), we found that the ⌬N-186 Vav SH3(820K) mutant showed an enhanced focus-forming ability. However, when we deleted the entire SH3/SH2/SH3 domain (⌬N-186 Vav⌬C), we were surprised to see that it was enhanced significantly in transforming activity.…”
Section: The Dh/ph/crd Is the Minimal Functional Transformingcontrasting
confidence: 99%
“…Previous studies reached conflicting conclusions regarding the importance of SH domains for Vav transforming activity. Whereas missense mutation of the SH domains caused a loss of activity (28,29), deletion of the SH domains indicated that these domains were dispensable for transforming activity. The basis for these different observations is not known.…”
Section: Phosphatidylinositol 3-kinase Does Not Greatly Enhance Vav Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Knock-down of Vav3 causes decreased receptor transactivation in cancer cells (19). As far as the role of Vav3 in the cell malignant transformation is concerned, the C-terminal SH3 domains appear to be indispensable to its cell transforming activity, whereas the N-terminal domains of Vav3 play a rather negative role (69,70). Due to the lack of GEF domain, Vav3.1 protein does not catalyze the exchange of GDP/GTP.…”
Section: Discussionmentioning
confidence: 99%
“…105,106 In addition, PKCd 107 and MAPK/ERK 108 phosphorylate hnRNP K on serine 302 and on serines 284/353, respectively. While hnRNP K-Vav interaction may be relevant for Vav-transforming activity, 109 the importance of hnRNP K phosphorylation by PKCd for hnRNP K function as regulator of mRNA metabolism is still unclear.…”
Section: Bcr/abl Rna Binding Proteins and Translational Regulation Omentioning
confidence: 99%